Factors influencing customer purchase decision of Nyanza bottling company (NBCL) products in Mwanza City. - Kyeju, Diana (Mzumbe university, 2024)
A dissertation submitted to Mzumbe University as partial fulfillment of the requirements of award of Masters Degree of Business Administration in Corporate Management (MBA-CM) of Mzumbe University